Investigating the Activities of Hungarian Vineyards in the Light of the Data from the Test Enterprise System 2005-2014 (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: grape and wine production; profitability; tangible assets; gross investment; net investment; investment subsidies; net liabilities